INTEGRATION OF THE AUTHORITY OF THE BUSINESS COMPETITION SUPERVISORY COMMISSION IN HANDLING CRIMES IN THE ECONOMIC FIELD - Rudianto Sahnitra Padang; T Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study discusses the importance of integrating the authority of the Business Competition Supervisory Commission (KPPU) in handling economic crimes in Indonesia. Currently, KPPU's authority is limited to administrative aspects, making it difficult to handle complex cases such as corruption and money laundering. It is necessary to expand KPPU's authority to investigate and prosecute perpetrators of economic violations that have an impact on business competition. Harmonization of regulations and increased coordination with institutions such as the Police and the KPK are also needed for more effective law enforcement. In addition, increasing the technical capacity and human resources of KPPU is expected to create a fair, conducive business environment that supports sustainable economic growth in Indonesia.